PERAN ORANGTUA DALAM MENGATASI DEGRADASI MORAL PADA REMAJA DI DESA BANGKALALOE KECAMATAN BONTORAMBA KABUPATEN JENEPONTO (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
The main problem of this research is how the role of parents in overcoming moral degradation in adolescents in Bangkalaloe Village, Bontoramba District, Jeneponto Regency. This study uses a descriptive qualitative research type located in Bangkalaloe Village, Bontoramba District, Jeneponto Regency. The research approach used is a guidance approach and a psychological approach. Data collection methods are observation, interviews, and documentation. Data analysis was obtained by researchers through interviews, questionnaires, and so on. The results of this study indicate that the steps taken by parents in overcoming moral degradation in adolescents in Bangkalaloe Village, Bontoramba District, Jeneponto Regency are providing supervision, instilling etiquette values, ​​and providing religious education. The obstacles faced by parents in overcoming moral degradation in adolescents in Bangkalaloe Village, Bontoramba District, Jeneponto Regency are the influence of gadgets, and the environment (friendship). The implications of this study are 1) Parents should pay more attention to their children's habits and playing environment so that there is no moral degradation in adolescents. 2) Parents are expected not to spoil their children by giving gadgets too early and to set a good example and care more about their children so that they avoid unwanted things.